2018
DOI: 10.7150/jca.25264
|View full text |Cite
|
Sign up to set email alerts
|

The significant prognostic value of ZEB1-AS1 up-regulation in patients with cancer.

Abstract: Zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) is a long non-coding RNA, which has found to unregulated in various kinds of cancer. This meta-analysis was conducted to demonstrate the association between ZEB1-AS1 expression levels and clinical outcome or prognosis of cancer patients.10 studies with 783 cancer patients were included in this meta-analysis by retrieving 5 databases (PubMed Central, EMBASE, Cochrane Library, Wiley Online Library and Medline).The result showed that overexpression of ZE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Increased ZEB1-AS1 expression has been demonstrated to contribute to the upregulated expression of ZEB1, the progression to EMT and cancer metastasis (20). Furthermore it is also significantly associated with tumor progression and patient survival, in many different types of cancer (25). However, few studies have examined other mechanisms that involve the oncogenic role of ZEB1-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ZEB1-AS1 expression has been demonstrated to contribute to the upregulated expression of ZEB1, the progression to EMT and cancer metastasis (20). Furthermore it is also significantly associated with tumor progression and patient survival, in many different types of cancer (25). However, few studies have examined other mechanisms that involve the oncogenic role of ZEB1-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of LncRNAs have the potential to act as biomarkers, Ni et al (2018) reported that ZEB1-AS1 resulting in shorter OS may be a useful biomarker for predicting a poor prognosis. Kim et al (2015) reported that HOTAIR is associated with human cervical cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, ZEB1-AS1 has been demonstrated to be overexpressed in glioma (16), colorectal cancer (17), gastric cancer (18), prostate cancer (19) Long non-coding RNA ZEB1-AS1 predicts a poor prognosis and promotes cancer progression through the miR-200a/ZEB1 signaling pathway in intrahepatic cholangiocarcinoma and cervical cancer (20). ZEB1-AS1 mainly functions as an oncogene and promotes cancer progression (21). ZEB1-AS1 upregulation has been shown to be associated with a poor prognosis in multiple types of cancer (22).…”
Section: Introductionmentioning
confidence: 99%